2016
DOI: 10.21276/sjams.2016.4.6.80
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative study of IV Labetalol and IV Hydralazine on mean arterial blood pressure changes in pregnant women with hypertensive emergency

Abstract: Abstract:The study was undertaken to compare lowering of blood pressure in pregnant women with hypertensive emergency by IV Labetalol and IV Hydralazine and to find out which drug produces better effect. This prospective type of interventional study was conducted in SMS Medical College, Jaipur among 226 women admitted with SBP ≥ 160 or DBP ≥ 110 mmHg or both. Women divided in 2 groups (113 each) devided randomly: Labetalol (Group-A), Hydralazine (Group-B).We measured the difference between pretreatment and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…in their comparative study on Labetalol and Hydrallazine found both drugs as effective and quick acting antihypertensive agents in severe pre eclampsia. 15 Numba in his study demonstrated Labetalol and Hydralazine effective and rapid anti-hypertensive agent in hypertension crises. 9 The time taken to lower blood pressure and number of doses of Hydralazine and Labetalol were similar in Numba study.…”
Section: Discussionmentioning
confidence: 97%
“…in their comparative study on Labetalol and Hydrallazine found both drugs as effective and quick acting antihypertensive agents in severe pre eclampsia. 15 Numba in his study demonstrated Labetalol and Hydralazine effective and rapid anti-hypertensive agent in hypertension crises. 9 The time taken to lower blood pressure and number of doses of Hydralazine and Labetalol were similar in Numba study.…”
Section: Discussionmentioning
confidence: 97%
“…A comparative study of IV Labetalol and IV Hydralazine on mean arterial blood pressure changes in pregnant women with hypertensive emergency by Swati et al [9] showed no significant difference between the changes in the mean arterial blood pressure after giving drugs; concluding that both the drugs were equally effective in management of severe hypertension in pregnancy.…”
Section: Discussionmentioning
confidence: 98%
“…A total of 320 articles were retrieved, of which 51 were included in the systematic review and 46 in the meta‐analysis. The PRISMA flow chart is depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%